Data analytics website for newspaper media (Back-end) - Chew, Shila Shi Ler (2017)
Data analytics refers to qualitative and quantitative techniques and processes used to enhance productivity and business gain. We build a data analytics website for newspaper media website to track their readers and understand their reader’s behaviour. To gather user requirement, we examine a free and open source web analytic called Piwik and a freemium web analytic service called Google Analytics in detail. To build the data collection component, JavaScript is used to track and send the data from the client to the server. To build the database, Microsoft SQL Server is used to store the data. We also point out various challenges that we face during the design and implementation phases and the solutions to the challenges. Finally, to ensure the quality of the data analytics website, we discuss about agile testing and the type of testing we used.